Plasma levels of autophagy regulator Rubicon are inversely associated with acute coronary syndrome - Grazide, Marie-Hélène; Ruidavets, Jean-Bernard; Martinet, Wim; Elbaz, Meyer; Vindis, Cécile (Frontiers in Cardiovascular Medicine, 2024)
The discovery of novel biomarkers that improve current cardiovascular risk prediction models of acute coronary syndrome (ACS) is needed for the identification of very high-risk patients and therapeutic decision-making. Autophagy is a highly conserved catabolic mechanism for intracellular degradation of cellular components through lysosomes. The autophagy process helps maintain cardiac homeostasis and dysregulated autophagy has been described in cardiovascular conditions. Rubicon (Run domain Beclin-1-interacting and cysteine-rich domain-containing protein) is a key regulator of autophagy with a potential role in cardiac stress.The aims of the present study were to assess whether changes in circulating Rubicon levels are associated with ACS and to evaluate the added value of Rubicon to a clinical predictive risk model.The study population included ACS patients (n = 100) and control subjects (n = 99) at high to very high cardiovascular risk but without known coronary event. Plasma Rubicon levels were measured in the whole study population by enzyme-linked immunosorbent assay. Multivariate logistic regression analyses established that Rubicon levels were inversely associated with ACS. A receiver operating characteristic curve analysis demonstrated that the addition of Rubicon This is a provisional file, not the final typeset article improved the predictive performance of the model with an increased area under the curve from 0.868 to 0.896 (p = 0.038).Conclusions: Plasma levels of the autophagy regulator Rubicon are associated with ACS and provide added value to classical risk markers for ACS.